ANALYSIS OF STOCK PERFORMANCE IN TECHNOLOGY SECTOR COMPANIES LISTED ON IDX 2021-2022: INDONESIA POINT OF VIEW - Fauzi, Muhammad Zufar; Rochmatullah, Mahameru Rosy (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The objective of this research is to examine how Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), Earnings Per Share (EPS), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Price Earnings Ratio (PER), and Price to Book Value (PBV) influence stock prices of technology sector companies listed on the Indonesia Stock Exchange (IDX) by the end of December 31, 2023. The study's target group is made up of 44 companies, with a total of 26 companies being chosen as samples through purposive sampling, based on certain criteria such as consistently issuing financial reports from the years 2021 to 2022. The data used in this research are secondary data collected from the financial reports of companies that are available on the official IDX website. The analysis technique employed is multiple linear regression, involving hypothesis testing through t-tests, F-tests, and R Square tests. The outcomes of this study reveal that the variables of EPS and PBV have a notable influence on stock prices. However, the NPM, DAR, ROA, ROE, DER, and PER variables do not display a significant impact on stock prices.